IMPLEMENTASI BUDAYA KOMPETITIF UNTUK PENINGKATAN MUTU LEMBAGA PENDIDIKAN DI MA`HAD AL-FIKRI MADRASAH ALIYAH NEGERI (MAN) 2 BLITAR - Astuti, Ika Widia (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2023)
The high value of needs demands that the millennial generation explore their potential, this is a new demand for every institution to create excellence both in the governance carried out and in the output of the institution. Ma`had is one of the breakthroughs in creating superior character, highly intellectual and having a good understanding of religion. The talent interest development program is a form of Ma`had's effort to create a competitive culture within students so that it can be applied in the school environment. Ma`had's role is highly expected to form a competitive advantage so that the process can be formed more easily and directed. Based on the background above, the author formulates it into the following problem formulation: 1) How to instill competitive advantage values ​​in Ma`had Al-Fikri (State Madrasah Aliyah) 2 Blitar, 2) How is the program implemented in creating a competitive culture in Ma`had Al -Fikri Madrasah Aliyah Negeri (MAN) 2 Blitar, 3) What are the implications of competitive culture for improving the quality of education at Ma`had Al-Fikri Madrasah Aliyah Negeri (MAN) 2 Blitar. This study uses a descriptive qualitative approach with a type of field study research, the informants used are Ma'had caregivers and students (students). Data collection was carried out by observation, interview and documentation methods. While the analysis was carried out using qualitative analysis in the form of data reduction, data presentation and drawing conclusions. This research results that, 1) There are seven types of competitive advantage embedded in Ma`had Al-Fikri, namely discipline, cleanliness, competitive, tenacity, language, visionary and sportsmanship. The seven values ​​are instilled through regulation, habituation, motivation, reward and punishment. 2) Ma`had Al-Fikri implements thirteen development programs through five techniques, namely repetition, habituation, development, training and program evaluation 3) The implications of a competitive culture for improving the quality of education can be seen in three ways, namely increasing academic achievement, increasing students' critical thinking in solving problems associated with the knowledge possessed, and increasing the quality of graduates.